Sosialisasi Standar Kualitas Air Bersih dan Solusi Penanganan Air Asam bagi Warga Perumahan Casadova - Saputra, Rizki Rachmad; Oksal, Efriyana; Alfanaar, Rokiy (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
Clean water quality is a crucial factor in people's lives, especially for residents of Casadova Housing, Menteng, Palangka Raya, who rely on shallow wells as their main source of water. The results of the study showed that well water in this area still contains an unpleasant odor and has a low pH level (4.5), which does not meet the standards of the Minister of Health Regulation No. 32 of 2017. Therefore, this community service activity aims to socialize clean water quality standards and provide solutions for handling acidic water for local residents. The implementation method includes counseling, demonstration of simple filtration technology, and technical assistance in improving water quality. The results of the activity showed an increase in residents' understanding of clean water standards and the application of simple technologies, such as the use of lime and aeration, to reduce the acidity level of water. It is hoped that this activity can improve the quality of life of residents with access to healthier and more consumable water.